CaMK4 Promotes Acute Lung Injury Through NLRP3 Inflammasome Activation in Type II Alveolar Epithelial Cell - Zhang, Tengyue; Li, Mengyuan; Zhao, Siyuan; Zhou, Mianjing; Liao, Huai; Wu, Haiyan; Mo, Xinyue; Wang, Hongxing; Guo, Chaohuan; Zhang, Hui; Yang, Niansheng; Huang, Yuefang (Frontiers in Immunology, 2022)
Abstract Background: Type II alveolar epithelial cell (AEC II), in addition to its roles in maintaining lung homeostasis, takes an active role in inflammatory response during acute lung injury (ALI). Ca2+/calmodulin-dependent protein kinase IV (CaMK4) activated by Ca2+/calmodulin signaling, has been implicated in immune responses. This study was to investigate the roles of CaMK4 in the development of ALI and the underlying mechanisms. Methods: CaMK4 inhibitor KN-93 was used to investigate the effects of CaMK4 on NLRP3 inflammasome activation. The effects of KN-93 on disease development of lipopolysaccharide (LPS)-induced ALI was also evaluated. The mechanism of CaMK4 on NLRP3 inflammasome activation was explored in human AEC II cell line A549 using KN-93 or CaMK4 siRNA. NLRP3 inflammasome activation was measured by histology immunofluorescence and Western blot. Cytokines of IL-1β and IL-18 were measured by ELISA. Results: Phosphorylation of CaMK4 and the expression of NLRP3 and Caspase-1 p20 were increased in the lungs of LPS-induced ALI mice, which was suppressed by KN-93 as measured by Western blot. Further, the activation of NLRP3 inflammasome was detected in AEC II of patients with acute respiratory distress syndrome (ARDS) and LPS-induced ALI mice. In vitro, inhibition or silencing CaMK4 in AEC II significantly inhibited NLRP3 inflammasome activation, resulting in reuducedIL-1β production. The inhibition of NLRP3 inflammasome and decreased IL-1β/IL-18 production by KN-93 led to reduced inflammatory infiltration and ameliorated lung injury in LPS-induced ALI mice. Conclusion: CaMK4 controls the activation of NLRP3 inflammasome in AEC II during LPS-induced ALI. CaMK4 inhibition could be a novel therapeutic approach to treat ALI.